Populist attitudes towards politics and science: how do they differ?. Issue 1 (31st December 2023) - Eberl, Jakob-Moritz; Huber, Robert A.; Mede, Niels G.; Greussing, Esther
ABSTRACT: While populist citizens' opposition to political elites has been intensively researched, populist criticism of other societal institutions, such as science, has only recently attracted public and scholarly attention. Political and science populism can both be understood as a set of ideas that revolve around an antagonism between a virtuous common people and an evil elite. However, political populism focuses on political power claims and challenges the political elites, whereas science populism addresses truth claims and criticizes the academic elites. Hence, conceptually, both populism variants pit the people against an elite – but they rely on different conceptualizations of the people and the elites, their authority claims, and the alleged (il)legitimacy of these claims. Yet, it remains unclear how distinct these two populism variants are empirically . We address this gap by comparing established scales for measuring individual attitudes towards both variants and provide three take aways: We recommend that scholars should (1) theorize and test the overlaps of the two populism variants, (2) acknowledge their differences and model these accordingly, and (3) consider which variant is better suited for predicting other attitudes or behaviours. Considering these takeaways would allow public opinion research to provide more fine-grained insights into the intricacies of populist attitudes within contemporary societies and challenges.